Coordination for EU Competitiveness - David Pinkus; Jean Pisani-Ferry; Simone Tagliapietra; Reinhilde Veugelers; Georg Zachmann; Jeromin Zettelmeyer (EconPol Forum, 2024)
The competitiveness of countries and that of firms are different concepts. EU GDP is stable at two-thirds of the US, but productivity growth has lagged since the 1990s. The EU does better on wealth equality and clean-tech export shares. The EU faces two supply-side disadvantages: high energy costs; and a fragmented internal market. We propose a strategy of "Coordination for Competitiveness": national-level policy coordination as an alternative to full EU-level integration. We illustrate this with two examples: energy policy coordination; and an EU-level ARPA.
Keywords: 330